Biotic control of LNAPL longevity - laboratory and field- scale studies - Emerson, Eric Douglas, author; De Long, Susan K., advisor; Sale, Thomas, advisor; Butters, Gregory, committee member (Colorado State University. Libraries, 2017)
Natural source zone depletion (NSZD) is an emerging strategy for managing light nonaqueous phase liquids (LNAPLs). Unfortunately, little is known about NSZD rates over extended periods of time, where heterogeneous redox conditions and changing LNAPL saturations may influence processes governing losses. Understanding long-term rates is central to anticipating LNAPL longevity under both natural and engineered conditions. Herein, laboratory and field-scale modeling studies were conducted to evaluate LNAPL longevity. Laboratory studies evaluated loss rates as a function of total contaminant concentration under sulfate-reducing (SR) and methanogenic (MG) conditions. Biotic and abiotic loss rates were determined via tracking biodegradation products and hydrocarbons in column effluents and produced gasses over time. Furthermore, compositional weathering of LNAPL was evaluated. Loss rates with elevated sulfate averaged 39.8 mmole carbon/day/m3 (±9.1 mmole carbon/day/m3). Once sulfate in the soil was depleted to influent water sulfate concentrations of 20 mg/L, subsequent average loss rates were 39.7 mmole carbon/day/m3 (±19.6 mmole carbon/day/m3). Overall, loss rates with and without elevated sulfate were similar. Furthermore, results suggested that loss rates are independent of LNAPL concentration over the range of 9,000 to 37,000 mg/kg and redox conditions observed. Loss rates independent of LNAPL concentrations indicated that biologically mediated NSZD follows zero-order kinetics over the range of conditions evaluated. Column loss rates were compared to field-measured loss rates assuming an LNAPL thickness of three meters. Given this assumption, mean observed early- and late-loss rates are 1.38 and 1.41 μmole carbon/m2/sec, respectively. Assuming decane as a representative LNAPL, observed loss rates are equivalent to 7890 and 8060 L/hectare/year. A column was sacrificed at the completion of the study. Predicted mass losses of the study equate to approximately 1% total initial LNAPL mass lost. Total petroleum hydrocarbons (TPH) soil analysis of initial and final grab samples of column soil did not detect significant mass losses. Moreover, no significant shifts in the LNAPL composition were seen during the course of the study. Mass losses in this range are difficult to accurately quantify via soil-phase hydrocarbon analyses, thus highlighting the utility of the approach used herein. An LNAPL longevity model (The Glide Path Model) was applied at a field site using a zero-order rate model for biological NSZD. LNAPL Longevity ranged from 35 to 105 years using a mean NSZD rate, plus or minus factors of 2 and ½, respectively. Active recovery was shown to have little effect on the longevity of LNAPL.
Keywords: glide path model; NSZD; anaerobic; rates; LNAPL